Homozygous loss of DIAPH1 is a novel cause of microcephaly in humans - Ercan-Sencicek, A Gulhan (Eur J Hum Genet, 2015)
The combination of family-based linkage analysis with high-throughput sequencing is a powerful approach to identifying rare genetic variants that contribute to genetically heterogeneous syndromes. Using parametric multipoint linkage analysis and whole exome sequencing, we have identified a gene responsible for microcephaly (MCP), severe visual impairment, intellectual disability, and short stature through the mapping of a homozygous nonsense alteration in a multiply-affected consanguineous family. This gene, DIAPH1, encodes the mammalian Diaphanous-related formin (mDia1), a member of the diaphanous-related formin family of Rho effector proteins. Upon the activation of GTP-bound Rho, mDia1 generates linear actin filaments in the maintenance of polarity during adhesion, migration, and division in immune cells and neuroepithelial cells, and in driving tangential migration of cortical interneurons in the rodent. Here, we show that patients with a homozygous nonsense DIAPH1 alteration (p.Gln778*) have MCP as well as reduced height and weight. diap1 (mDia1 knockout (KO))-deficient mice have grossly normal body and brain size. However, our histological analysis of diap1 KO mouse coronal brain sections at early and postnatal stages shows unilateral ventricular enlargement, indicating that this mutant mouse shows both important similarities as well as differences with human pathology. We also found that mDia1 protein is expressed in human neuronal precursor cells during mitotic cell division and has a major impact in the regulation of spindle formation and cell division.